Effects of Blended Learning in Physical Education among University Students: A Systematic Review - Chen Wang; Roxana Dev Omar Dev; Kim Geok Soh; Nasnoor Juzaily Mohd Nasiruddin; Yuansheng Wang (MDPI AG, 2022)
(1) Background: Blended learning (BL) models have attracted the attention of university teachers and students worldwide in recent years. However, systematic reviews related to the effectiveness of BL in university physical education are lacking. (2) Purpose: Therefore, this study aimed to evaluate the effects of BL in physical education among university students. (3) Methods: Searches were conducted in the following five databases: Web of Science, Scopus, PubMed, EBSCOhost (SPORTDiscus), and China National Knowledge Infrastructure (CNKI), and 18 articles met the inclusion criteria and were selected. The PEDro scale was used to assess the methodological quality of the selected studies and the quality of this study was fair (range 4-5). (4) Results: All reported sports included basketball (n = 6), badminton (n = 3), dance (n = 3), volleyball (n = 1), yoga (n = 1), aerobics (n = 1), Taiji (n = 1), swimming (n = 1), and tennis (n = 1). Seventeen studies described the effect of BL on students' motor skills, and the results showed that BL had a greater effect on basic skills, but the improvement was not significant for combination techniques. There were three studies related to physical fitness. Studies have observed significant effects on lung capacity (n = 1), sit and reach (n = 1), pull-ups (n = 1), 1000 m (n = 3), and 800 m (n = 1). However, there was no significant difference in body weight (n = 1) or standing long jump (n = 1). In addition, two articles examined the impact of BL on sitting up, but the findings were the opposite. Six studies reported on exercise attitude and the results demonstrated that BL can significantly improve students' learning attitude, target attitude, behavioral cognition, and emotional experience. However, the two articles produced different results in behavioral habits. Other results, such as satisfaction and interest in learning, were also popular topics regarding BL and were found to have improved significantly.